Plasma lipidome reveals critical illness and recovery from human Ebola virus disease - Kyle, J. E.; Burnum-Johnson, K. E.; Wendler, J. P.; Eisfeld, A. J.; Halfmann, Peter J.; Watanabe, Tokiko; Sahr, Foday; Smith, R. D.; Kawaoka, Y.; Waters, K. M.; Metz, T. O. (Proceedings of the National Academy of Sciences - PNAS, 2019)
Ebola virus disease (EVD) often leads to severe and fatal outcomes in humans with early supportive care increasing the chances of survival. Profiling the human plasma lipidome provides insight into critical illness as well as diseased states, as lipids have essential roles as membrane structural components, signaling molecules, and energy sources. Here we show that the plasma lipidomes of EVD survivors and fatalities from Sierra Leone, infected during the 2014–2016 Ebola virus outbreak, were profoundly altered. Focusing on how lipids are associated in human plasma, while factoring in the state of critical illness, we found that lipidome changes were related to EVD outcome and could identify states of disease and recovery. Specific changes in the lipidome suggested contributions from extracellular vesicles, viremia, liver dysfunction, apoptosis, autophagy, and general critical illness, and we identified possible targets for therapies enhancing EVD survival.